Analisa Performa SOFC Proton ElektrolitSistem Hibrid dengan Bahan Bakar Alternatif - Amir, Nizar; Purnomo, Reymond (Jurnal Rekayasa Mesin, 2013)
This paper studied the modeling of proton conducting electrolyte SOFC hybrid system fueled by biofuel. The hybrid system consist of a proton conducting electrolyteSOFC stack, a gas turbine, a combustor, two external reformers, two compressors and heat exchangers. The results of study show that power of protonconducting electrolyte SOFC stack and also gas turbine power output when mixing methane with biofuel in externally reformed proton SOFC hybrid system ishigher than pure methane, vice versa, the system efficiency is lowerthan pure methane as a fuel. However, when mixing methane with biofuel, the system efficiency increases with increasing operating pressure.